Improvement of Intrapreneurship Behavior in Higher Education - Novie Rachma Yulia; Sri Setyo Iriani; Andre Dwijanto Witjaksono; Siti Sri Wulandari (IKIP PGRI Bojonegoro, 2022)
Abstract: Educational Development Contribution is no longer the only source of income from universities. Universities are expected to have a Business Center as a solution to overcome financing problems and increase income as well as welfare for organizational members within the university. This Business Center can run if members of the organization have an entrepreneurial spirit and intrapreneurship behavior. This research aims to explore the transformational leadership style and entrepreneurial character as factors that can increase intrapreneurship behavior (Behavioral Intrapreneurship) in organizational members at a private university located in West Surabaya. The research uses a qualitative method with a case research approach and quantitative by the percentage method for descriptive analysis on each variable. In-depth interviews were conducted with key informants and questionnaires for other respondents. This is intended to be able to explore phenomena that exist in the field. The results of this research indicate that the rector at the university has a transformational leadership style while the lecturers and employees at the university have an entrepreneurial character and intrapreneur behavior. This research concludes that the transformational leadership style of the leader contributes to the formation of intrapreneurship behavior in the university environment. Abstrak: Kontribusi Pengembangan Pendidikan bukan lagi satu-satunya sumber pendapatan dari perguruan tinggi. Perguruan tinggi diharapkan memiliki Pusat bisnis sebagai solusi untuk mengatasi masalah pembiayaan dan meningkatkan pendapatan serta kesejahteraan bagi anggota organisasi di lingkungan perguruan tinggi. Pusat Bisnis ini dapat berjalan jika anggota organisasi memiliki jiwa kewirausahaan dan perilaku intrapreneurship. Penelitian ini bertujuan untuk mengeksplorasi gaya kepemimpinan transformasional dan karakter wirausaha sebagai faktor yang dapat meningkatkan perilaku intrapreneurship (Behavioral Intrapreneurship) pada anggota organisasi pada sebuah perguruan tinggi swasta yang berlokasi di Surabaya Barat. Penelitian ini menggunakan metode kualitatif dengan pendekatan penelitian kasus dan kuantitatif dengan metode persentase untuk analisis deskriptif pada masing-masing variabel. Wawancara mendalam dilakukan dengan informan kunci dan kuesioner kepada responden lain. Hal ini dimaksudkan untuk dapat menggali fenomena-fenomena yang ada di lapangan. Hasil penelitian ini menunjukkan bahwa rektor di universitas memiliki gaya kepemimpinan transformasional sedangkan dosen dan karyawan di universitas memiliki karakter kewirausahaan dan perilaku intrapreneur. Penelitian ini menyimpulkan bahwa gaya kepemimpinan transformasional pemimpin berkontribusi terhadap pembentukan perilaku intrapreneurship di lingkungan universitas.